ZAKAT AND SDG 6: A CASE STUDY OF BAZNAS, INDONESIA - Fahmi Ali Hudaefi; Abdul Aziz Yahya Saoqi; Hidayaneu Farchatunnisa; Ulfah Lathifah Junari (Bank Indonesia, 2020)
Recent zakat distribution by the National Board of Zakat, Republic of Indonesia (BAZNAS), such as the construction of private lavatories for underprivileged households, have contributed to the idea that zakat promotes the sustainability of clean water and sanitation (SDG 6). However, this notion demands detailed academic explanation to better understand it systematically. This paper thus aims to explore the degree to which the toilet construction project has benefitted its recipients. This case study of BAZNAS’s project in Kendel, Boyolali, Indonesia, employs a qualitative approach based on participatory observation and semi-structured interviews. The findings explain the perspectives of local community after receiving the assistance, including the identification of reduction in numbers of local people affected by diarrhoea. This information may validate the relationships between health, water and sanitation. Furthermore, the findings capture the involvement of local government in the project execution. Thus, social and practical implications are revealed by this study. This study pioneers the establishment of scholarly-based evidence about the programme of individual toilet construction executed by BAZNAS, and about the perspectives of its recipients in the wake of receiving the aid.